EEG Correlates of Long-Distance Dependency Formation in Mandarin Wh-Questions - Lo, Chia-Wen; Brennan, Jonathan R. (Frontiers in Human Neuroscience, 2021)
Event-related potential components are sensitive to the processes underlying how questions are understood. We use so-called "covert" wh-questions in Mandarin to probe how such components generalize across different kinds of constructions. This study shows that covert Mandarin wh-questions do not elicit anterior negativities associated with memory maintenance, even when such a dependency is unambiguously cued. N=37 native speakers of Mandarin Chinese read Chinese questions and declarative sentences word-by-word during EEG recording. In contrast to prior studies, no sustained anterior negativity (SAN) was observed between the cue word, such as the question-embedding verb "wonder", and the in-situ wh-filler. SANs have been linked with working memory maintenance, suggesting that grammatical features may not impose the same maintenance demands as the content words used in prior work.